1979
DOI: 10.2118/7591-pa
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Oilwell Cementing Compositions in Geothermal Wells

Abstract: Just afew years ago, there existed a great uncertainty regarding the durability of oi/well cements in geothermal wells. Limited, and at times apparently unreliable, information suggested that conventional well cements may not be sufficiently resistant to geothermal well fluids and temperatures for the expected 20-or 30-year service life of the average geothermal well. Therefore, we began to investigate the performance of numerous oi/well cementing compositions in actual geothermal environments.Duplicate sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This was confirmed by the natural CO 2 producer [ 9 ] and by pilot storage wells [ 10 ] that proved to operate without issues for extended periods of time. Cement sample well exposure tests also confirmed the OPC/silica HT blend to be stable for extended periods of time at temperatures below 200 °C [ 11 ]. In this study, formulations with higher silica content were shown to be preferential for good mechanical performance and lower porosity of cement after up to a year of field exposure.…”
Section: Introductionmentioning
confidence: 99%
“…This was confirmed by the natural CO 2 producer [ 9 ] and by pilot storage wells [ 10 ] that proved to operate without issues for extended periods of time. Cement sample well exposure tests also confirmed the OPC/silica HT blend to be stable for extended periods of time at temperatures below 200 °C [ 11 ]. In this study, formulations with higher silica content were shown to be preferential for good mechanical performance and lower porosity of cement after up to a year of field exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The high temperatures pose challenges while the well is being drilled and completed and after construction has been completed. [1][2][3] In a geothermal well, carbon dioxide (CO 2 ) may be encountered in some of the formations, which can be a serious corrosive threat to both the cement and the casing in the well.…”
Section: Introductionmentioning
confidence: 99%